Polyphasic hydrothermal and meteoric fluid regimes during the growth of a segmented fault involving crystalline and carbonate rocks (Barcelona Plain, NE Spain). Issue 1 (28th February 2013) - Cantarero, I.; Travé, A.; Alías, G.; Baqués, V.
Abstract A polyphasic tectonic‐fluid system of a fault that involves crystalline and carbonate rocks (Hospital fault, Barcelona Plain) has been inferred from regional to thin section scale observations combined with geochemical analyses. Cathodoluminescence, microprobe analyses and stable isotopy in fracture‐related cements record the circulation of successive alternations of hydrothermal and low‐temperature meteoric fluids linked with three main regional tectonic events. The first event corresponds to the Mesozoic extension, which had two rifting stages, and it is characterized by the independent tectonic activity of two fault segments, namely southern and northern Hospital fault segments. During the Late Permian‐Middle Jurassic rifting, these segments controlled the thickness and distribution of the Triassic sediments. Also, dolomitization was produced in an early stage by Triassic seawater at shallow conditions. During increasing burial, formation of fractures and their dolomite‐related cements took place. Fault activity during the Middle Jurassic–Late Cretaceous rifting was localized in the southern segment, and it was characterized by hydrothermal brines, with temperatures over 180°C, which ascended through this fault segment precipitating quartz, chlorite, and calcite. The second event corresponds to the Paleogene compression (Chattian), which produced exhumation, folding and erosion, favouring the percolation of low‐temperature meteoric fluids which produced the calcitization of the dolostones and of the dolomite cements. The third event is linked with the Neogene extension, where three stages have been identified. During the syn‐rift stage, the southern segment of the Hospital fault grew by tip propagation. In the relay zone, hydrothermal brines with temperature around 140°C upflowed. During the late postrift, the Hospital fault acted as a unique segment and deformation occurred at shallow conditions and under a low‐temperature meteoric regime. Finally, and possibly during the Messinian compression, NW‐SE strike‐slip faults offset the Hospital fault to its current configuration.